Electronic and magnetic properties regulation of finite to infinite half sandwich organo-transition-metal-complexes functionalized graphene. Issue 100 (13th October 2016) - Zhang, Xiuyun; Bian, Yajie; Sun, Weikang; Hu, Ting; Liu, Yongjun
Abstract : Total band gaps (Δ t ) and band gaps of free "graphene", ignoring impurity bands of TM n OLs (Δ g ). Abstract : Using first principles calculations, we systematically investigated the structural, electronic and magnetic properties of half-sandwiched organo-ligand (OL)-transition metal (TM) ligands functionalized single-layer graphene (SLG) with diverse arrangement patterns, including zero-dimension (0D) TM n OL– (OL: Bz = C6 H6, Np = C10 H8, Ant = C14 H10, TM = Ti, Cr, Mn, Fe, n = 1, 2, 3) and 1D organometallic molecule wires, [TMC4 H2 ]∞ and [TM2 C6 H2 ]∞ . In the studied structures, most TM atoms favor the hollow site of graphene, while a few favor the top site. All systems are chemically stable and the half-sandwiched TM n OL– ligands are covalently bonded with graphene. Interestingly, most TM n OL@Gs are ferromagnetic with the largest magnetic moment of 2.96 μ B for Cr3 Ant@G77 . In addition, ferri–ferromagnetic properties are found for Fe2 Np@G77 and Fe3 Ant@G77, while antiferromagnetic properties are found for Ti3 Ant@G77 . With the exception of FeBz@G33, all the TMBz@G33 and TMBz@G66 are semiconductors and the band gap of CrBz@G33 is as large as ∼1.0 eV. As for FeBz@G, the gap for graphene at the Dirac point is opened to 0.673 eV, 0.581 eV and 0.148 eV within the 4 × 4, 5 × 5 and 6 × 6 supercell, respectively. Moreover, the band gaps for TM2 Np@G77 and TM3 Ant@G77 are largely reduced due to the increased coverage of TM atoms. Furthermore, robust magnetic and electronic properties are found for [TMC4 H2 ]∞ @G and [TMC6 H2 ]∞ @G, in which the magnetic moment of [MnC4 H2 ]∞ @G and [FeC6 H2 ]∞ @G per cell unit is rather large at around 2.36 μ B and 4.43 μ B, respectively. Most [TMC4 H2 ]∞ @Gs and [TMC6 H2 ]∞ @Gs are metals, while [MnC4 H2 ]∞ @G is transformed to be a semiconductor.